Injectable Mesenchymal Stem Cell‐Laden Matrigel Microspheres for Endometrium Repair and Regeneration. Issue 8 (12th June 2021) - Xu, Bing; Cao, Yuanxiong; Zheng, Zheng; Galan, Edgar A.; Hu, Zhiwei; Ge, Jun; Xing, Xinhui; Ma, Shaohua
Abstract: Endometrial injury and intrauterine adhesions are increasingly reported in recent years; however, treatment options remain limited. Intravenous injection of mesenchymal stem cells (MSCs) for endometrium regeneration has limited effectiveness as the retention rate of transplanted cells is low. Hydrogel‐based tissue‐engineered solutions, such as MSC‐seeded bioscaffolds, are reported to increase retention rates; however, a less invasive alternative is still desirable. 560‐µm homogeneous Matrigel microspheres are fabricated, loading them with about 1500 MSCs and injecting them into the injured endometria of rats' uteri. This minimally invasive procedure is proved to significantly increase endometrium thickness by over onefold after 21 d ( p < 0.0001) and fertility rates from 25% to 75% in impaired and repaired uteri ( p < 0.001), respectively. This study provides a minimally invasive alternative to endometrium repair with the promise to establish a broad‐spectrum technique for MSC transplantation. Abstract : Injection of homogeneous mesenchymal stem cell (MSC)‐laden Matrigel microspheres provides a less invasive and more effective procedure to transplant MSCs. The transplanted MSC/Matrigel microspheres enable the development of blood vessels and uterine glands and increase endometrial thickness and fertility rates.